Effect of TIPA on Chloride Immobilization in Cement-Fly Ash Paste. (16th July 2018) - Ma, Baoguo; Zhang, Ting; Tan, Hongbo; Liu, Xiaohai; Mei, Junpeng; Jiang, Wenbin; Qi, Huahui; Gu, Benqing
Abstract : Utilization of sea sands and coral aggregate for concrete in ocean construction is increasingly attracting the attention all over the world. However, the potential risk of steel corrosion resulting from chloride in these raw materials was one of the most concerned problems. To take this risk into account, chloride transporting to the surface of steel should be hindered. The formation of Friedel's salt in hydration process is widely accepted as an effective manner for this hindrance. In this study, an attempt to hasten the formation of Friedel's salt by adding triisopropanolamine (TIPA) was done in the cement-fly ash system, with intention to chemical bind chloride, and the chloride-binding capacity at 60 d age was examined. The results show that TIPA can enhance the chloride-binding capacity of cement-fly ash paste at 60 d age, and the reason is that the formation of Friedel's salt can be accelerated with addition of TIPA. The mechanism behind is revealed as follows: on the one hand, the accelerated cement hydration provides more amount of calcium hydroxide to induce the pozzolanic reaction of fly ash, which can hasten the dissolution of aluminum into liquid phase; on the other hand, TIPA can directly hasten the dissolution of aluminum in fly ash, offering more amounts of aluminum in liquid phase. In this case, the aluminum/sulfate (Al/S) ratio was obviously increased, benefiting the formation of Friedel's salt in hydration products. Such results would expect to provide useful experience to promote the chloride-binding capacity of cement-fly ash system.